2012
DOI: 10.14214/sf.65
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of herbaceous vegetation to gap opening in a Central European beech stand

Abstract: T. 2012. Dynamic response of herbaceous vegetation to gap opening in a Central European beech stand. Silva Fennica 46(1): 53-65.Herbaceous ground vegetation in artificially-created gaps was studied in a managed beech (Fagus sylvatica L.) forest over a period of eight years in Northern Hungary, Central Europe. These gaps were being used as an alternative to the regular shelterwood system to create uneven-aged stands. The effects of gap size (15 and 40 m diameter) and canopy openness on herbaceous species coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 47 publications
6
36
0
2
Order By: Relevance
“…Long-term conservation management positively influenced physical and chemical properties of soil, so that environmental conditions in TCM were similar to those in Un site. Studies have proved that destruction affected soil properties, which resulted in forest fragmentation, and finally changed vegetation and soil nutrient contents in forest (Kelemen et al 2012). The canopy of trees and shrubs in FCM and D sites was almost half of that in Un and TCM sites.…”
Section: Physical and Chemical Properties Of Soil And Canopy Percentamentioning
confidence: 99%
“…Long-term conservation management positively influenced physical and chemical properties of soil, so that environmental conditions in TCM were similar to those in Un site. Studies have proved that destruction affected soil properties, which resulted in forest fragmentation, and finally changed vegetation and soil nutrient contents in forest (Kelemen et al 2012). The canopy of trees and shrubs in FCM and D sites was almost half of that in Un and TCM sites.…”
Section: Physical and Chemical Properties Of Soil And Canopy Percentamentioning
confidence: 99%
“…Ujházy et al (2005) found relatively low species turnover in primeval fir-beech forest compared to commercial forests in Slovakia in all three developmental stages of forest dynamics -the growing, optimum and decay stages were differentiated rather by the value of abundance and dominance then by changes in diversity. Applying this theoretical knowledge in the practice of sustainable forest management (using only small regeneration areas) can support the conservation of the diversity of the herbaceous layer and prevent invasive or ruderal species with strong competitive abilities (Kelemen et al 2012). Thus, the application of retention forestry in the frame of conservation planning for forested protected areas can be considered as a good support tool for integrating conservation targets to forest management practice (Fedrowitz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the overstory and the understory is better revealed in mesic forests (Burrascano et al 2011, Graae and Heskajer 1997, Härdtle et al 2003, Kelemen et al 2012, Standovár et al 2006. In case of dry, oak dominated forests, our knowledge is more incomplete, in spite of their economic and conservational significance.…”
Section: Introductionmentioning
confidence: 99%